Amantadine Resistant of Indonesian H5N1 Subtype Influenza Viruses During 2003-2008 - NI LUH PUTU INDI DHARMAYANTI; FERA IBRAHIM; AMIN SOEBANDRIO (Microbiology Indonesia, 2010)
The M2 protein of 146 avian influenza (AI) viruses data available in public database (NCBI), including 20 AI isolates used in this study, were sequenced at the M2 protein to find out the probability of mutation and the increase of resistance to amantadine after more than 5 years of their circulation in Indonesia. The results showed that during 2003-2008, around 62.58% (92/147) AI viruses in Indonesia have showed resistance to amantadine and 10 of them have dual mutations at V27A and S31N.